FLUCTUATIONS OF PLANKTON POPULATION IN OX-BOW LAKE IN NADIA DISTRICT (WEST BENGAL) - Das, S; Sau, S K; DASGUPTA, M; TRIVEDI, R K (Journal of the Inland Fisheries Society of India, 2020)
A study was carrierd out to assess the diversity, abundance and fluctuations of plankton in an ox-bow lake in West Bengal. Total 21 genera of phytoplankton belonging to Chlorophyceae, Myxophyceae, Bacillariophyceae and Euglenophyceae and 21 genera of zooplankton of Copepoda, Cladocera, Rotifera, Ostracoda and Rhizopoda were identified from the lake . Total plankton varied from 20 to 505 nos. l-1 and showed two peaks, one in April and the other in February. Chlorophyceae and Myxophyceae were dominant among phytoplankton and Copepoda was abundant among zooplankton. Key words: Plankton, diversity, abundance, oxbow lake